STRATEGI LOCK-IN LOYALTY STARBUCKS DALAM MEMBENTUK LOYALITAS KONSUMEN: ANALISIS PERILAKU KONSUMEN - Abdul Muin; Darul Fikri; Silvy Dewi Anggraini; Siti Fatmawati; Ronika Cahya Putri Ayu; Dinda Elisiya; Syakila Dwi Ramadhani (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
The rapid growth of the Food and Beverage (F&B) industry in Indonesia has intensified competition among coffee brands, making customer loyalty an important factor in maintaining business sustainability. This study aims to analyze the effectiveness of Starbucks' lock-in loyalty strategy in building customer loyalty in Indonesia. The research employed a qualitative approach using a case study method. Data were collected from various digital sources, including Starbucks' official social media accounts, company websites, the Starbucks Rewards application, and supporting documents. The data were analyzed using content analysis techniques to identify the forms and implementation of lock-in loyalty strategies. The results show that Starbucks strengthens customer loyalty through several integrated strategies, including rewards programs, service personalization, digital applications, and transaction convenience. These strategies create both functional and emotional benefits that encourage repeat purchases and long-term customer attachment. In addition, customer loyalty is influenced by consumer behavior factors such as culture, social class, reference groups, and electronic word of mouth (E-WOM). The combination of these factors enables Starbucks to maintain customer loyalty and strengthen its competitive position in the increasingly competitive coffee industry.